The effect of cutting regime and genotype on growth, seed yield, seed quality and herbage yield of seven Urochloa (syn. Brachiaria) grass genotypes in the Adamawa region of Cameroon - Ojong, N.; Takor, M.; Egbe, A.; Bechem, E.; Etchu, K.; Mutai Collins, K. (Wiley, 2024)
The performance of seven Urochloa grass genotypes (three worldwide cultivars cv. Basilisk, cv. Piata, cv. Xaraes and four landrace cv. Adamaoua1, cv. Adamaoua2, cv. North1 and cv. North2) subjected to two cutting regimes (mid-June cut and mid-July cut) was evaluated for regrowth characteristics, seed yields, seed quality and herbage production in 2020 and 2021 cropping seasons at Wakwa, Ngaoundere, Cameroon. This divergence in harvesting practices raises concerns regarding the effectiveness and efficiency of forage utilization, as well as the potential impact on livestock productivity and sustainable farming systems. A split plot design with five replications and a 1-year-old sward was used for the study. In both years, genotypes were significantly different for plant height and tiller numbers at 12 weeks after cutting (P ≤ 0.007). In 2020, the dry matter yield (DMY) ranged between 8.78 t/ha (cv. Piata) and 12.75 t/ha (cv. Xaraes) for June cut regrowth and between 7.69 t/ha (cv. Piata) and 10.26 t/ha (cv. Xaraes) for July cut regrowth. In 2021, DMY ranged between 6.06 t/ha (Adamaoua2) and 13.95 t/ha (cv. Xaraes) for the June cut and between 6.55 t/ha (cv. Adamaoua2) and 10.47 t/ha (cv. Basilisk) for the July cut. For flowering behavior and seed yields, Basilisk flowered earliest while cv. Xaraes flowered latest. In 2020, seed yields were 74.80 kg/ha and 107.72 kg/ha for June cut and July cut regrowth, respectively, whereas in 2021, seed yields were 331 kg/ha and 431 kg/ha for June cut and July cut regrowth, respectively. cv. Adamaoua1 produced the highest seed yield in both years. The cutting regimes evaluated in this study were indifferent for DMY and seed yield.